A Review on Metal- and Metal Oxide-Based Nanozymes: Properties, Mechanisms, and Applications - Liu, Qianwen; Zhang, Amin; Wang, Ruhao; Zhang, Qian; Cui, Daxiang (Nano-Micro Letters, 2021)
Since the ferromagnetic (Fe3O4) nanoparticles were firstly reported to exert enzyme-like activity in 2007, extensive research progress in nanozymes has been made with deep investigation of diverse nanozymes and rapid development of related nanotechnologies. As promising alternatives for natural enzymes, nanozymes have broadened the way toward clinical medicine, food safety, environmental monitoring, and chemical production. The past decade has witnessed the rapid development of metal- and metal oxide-based nanozymes owing to their remarkable physicochemical properties in parallel with low cost, high stability, and easy storage. It is widely known that the deep study of catalytic activities and mechanism sheds significant influence on the applications of nanozymes. This review digs into the characteristics and intrinsic properties of metal- and metal oxide-based nanozymes, especially emphasizing their catalytic mechanism and recent applications in biological analysis, relieving inflammation, antibacterial, and cancer therapy. We also conclude the present challenges and provide insights into the future research of nanozymes constituted of metal and metal oxide nanomaterials. Highlights: 1 The characteristics of metal- and metal oxide-based nanozymes with diverse construction are dissertated. 2 The intrinsic properties and catalytic mechanism of metal- and metal oxide-based nanozymes are discussed. 3 The recent applications of metal- and metal oxide-based nanozymes in biological analysis, relieving inflammation, antibacterial, and cancer therapy are reviewed.